PENGARUH STRATEGI DIFERENSIASI PELAYANAN TERHADAP KEPUASAN KONSUMENINDUSTRI JASA PERHOTELAN (Studi Pada Hotel The Hills Kota Bukittinggi) - Linda, Wulandari Afrima; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Diferensiasi is action design to with refer to difference meaning to differentiate company bargain with competitor bargain (Kotler, 2002). Company do/conduct diferensiasi to all his/its competitor is when he/she succeed to present unique assessed important by buyer, apart from low price tender (Porter, 2002). This matter is such here is how a company of a kind applying strategy diferensiasi which later become one of identity in getting excellence compete it. This matter is which ought to be owned by service firm, in order to they do not become a commodity of is of equal which cannot be differentiated with other company. To consumer in order to consider service bargain which on the market that way a lot of competitor offering same thing, so that the consumer get experience marketing which cannot be forgotten so that make our company as single capable to provide such as those which they expect.This research is done/conducted in region of Bukittinggi with object of research that is Hotel of The Hill Bukittinggi which of have location in Road;Street. Barrel of Grandfather of Bandaro No.18, Bukittinggi. Hotel The Hill Bukittinggi choose as location of research of because Hotel The Hill Bukittinggi have an affair that is seen from result of goals and realize from sale of huniar of room;chamber every year nya experience of fluaktuasi from year 2012 - 2015 and also problems of satisfaction of consumer seenly by is data of complain of consumer experiencing of improvement every year 2012-2015. This matter make writer interested to see whether/what there is influence of strategy of diferensiasi to satisfaction of consumer of at Hotel The Hill Bukittinggi and chosen object of Hotel The Hill Bukittinggi as research place.In this research is methodologies used by is quantitative and descriptive with program SPSS, where sampel which pulled by writer is consumer visiting Hotel The Hill by sampel 100 people of responder which got by using formula Slovin.From result analyse data covering validity test, reabilitas, and doubled linear regresi, strategy of diferensiasi of service have an effect on to consumer satisfaction. Each owning indicator which each other be interconnected and have an effect on positive to satisfaction of consumer in using service of at room;chamber of the hotelKeyword: different service strategy and consumer satisfaction